The Hydropathy Index of the HCDR3 Region of the B-Cell Receptor Identifies Two Subgroups of IGHV-Mutated Chronic Lymphocytic Leukemia Patients With Distinct Outcome - Rodríguez-Caballero, Arancha; Fuentes Herrero, Blanca; Oliva Ariza, Guillermo; Criado, Ignacio; Alcoceba, Miguel; Prieto, Carlos; Pérez Caro, María; García-Montero, Andrés C.; González Díaz, Marcos; Forconi, Francesco; Sarmento-Ribeiro, Ana Bela; Almeida, Julia; et al. (Frontiers in Oncology, 2021)
The HCDR3 sequences of the B-cell receptor (BCR) undergo constraints in length, amino acid use and charge during maturation of B-cell precursors and after antigen encounter, leading to BCR and antibodies with high affinity to specific antigens. Chronic lymphocytic leukemia consists of an expansion of B-cells with a mixed immature and “antigen-experienced” phenotype, with either a mutated (M-CLL) or unmutated (U-CLL) tumor BCR, associated with distinct patient outcomes. Here, we investigated the hydropathy index of the BCR of 138 CLL patients and its association with the IGHV mutational status and patient outcome. Overall, two clearly distinct subgroups of M-CLL patients emerged, based on a neutral (mean hydropathy index of -0.1) vs negatively charged BCR (mean hydropathy index of -1.1) with molecular features closer to those of B-cell precursors and peripheral/mature B-cells, respectively. Despite M-CLL with neutral HCDR3 did not show traits associated with a mature B-cell repertoire, important differences in IGHV gene usage of tumor cells and patient outcome were observed in this subgroup of patients once compared to both U-CLL and M-CLL with negatively charged HCDR3 sequences. Compared to M-CLL with negatively charged HCDR3 sequences, M-CLL with neutral HCDR3 sequences showed predominance of men, more advanced stages of the disease and a greater frequency of genetic alterations – e.g. del(17p) – together with a higher rate of disease progression and shorter time to therapy (TTT), independently of other prognostic factors. Our data suggest that the hydropathy index of the HCDR3 sequences of leukemia CLL cells allows the identification of a subgroup of M-CLL with intermediate prognostic features between U-CLL and the more favorable subgroup of M-CLL with a negatively charged BCR.